2021
DOI: 10.2147/jaa.s295228
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to Common Allergens Among Children with Asthma and Allergic Rhinitis in Qatar

Abstract: Background: Childhood asthma (A) and allergic rhinitis (AR) are common in Qatar. Aeroallergens sensitization is integral in disease pathogenesis and clinical presentation. Determining sensitization patterns assists clinicians in tailoring an efficient medical management. Objective: To determine the aeroallergen sensitization pattern and relationship to clinical parameters. Methods: A retrospective review of children (2-14-years) files with i) Pediatric Allergist/or Pulmonologist confirmed-diagnosis of A, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
6
4
0
1
Order By: Relevance
“…Family history was quite positive in patients with childhood asthma and allergic rhinitis and common aeroallergens including HDMs, cats, and Alternaria were common in young children, while animal allergens were common in older children. Our observation is consistent with the results described above (Zahraldin et al 2021 ) . Our observation is consistent with the results described above.…”
Section: Discussionsupporting
confidence: 94%
“…Family history was quite positive in patients with childhood asthma and allergic rhinitis and common aeroallergens including HDMs, cats, and Alternaria were common in young children, while animal allergens were common in older children. Our observation is consistent with the results described above (Zahraldin et al 2021 ) . Our observation is consistent with the results described above.…”
Section: Discussionsupporting
confidence: 94%
“…Some studies have demonstrated that allergic diseases are more common in females than in males [23,24] , while other studies have reported higher allergen sensitization rates in men than in women [25,26] . We found no sex differences in the positivity rate of inhaled and food allergens, which is consistent with the ndings in some previous studies [27,28] . The reason for the difference remains unclear and further studies should be conducted to explain any observed sex-related differences.…”
Section: Discussionsupporting
confidence: 93%
“…China has the largest population around the world and wide geographical distribution in Asia, which results in significant individual heterogeneity of the associations between sensitization panels and clinical performance. 17 Though several studies have confirmed the causal associations of atopic sensitization with asthma, rhinitis or dermatitis in China, 30 , 31 most of them just focused on specific allergens on the risk of clinical symptoms and neglected the combined effects of allergens. Therefore, it's necessary to identify sensitization clusters of common allergens and further to investigate their complex relationship with allergy symptoms among the Chinese population using such machine learning methodologies.…”
Section: Discussionmentioning
confidence: 99%